Sifat Fisik dan Mikroanatomi Daging Kerbau dan Sapi pada Umur yang Berbeda - Mendrofa, V. A.; Priyanto, R.; Komariah, Komariah (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The consumer perceptions upon meats from buffalo and cattle may vary due to differences in their physical and microanatomycal characteristics. This study was aimed at comparing physical (pH, water holding capacity, tenderness, and cooking loss) and histology (muscle fibre surface, muscle bundle area, sum of muscle/ muscle bundle, muscle area/ musle bundle, distance between muscle bundle and connective tissue/ muscle bundle) of meat for buffalo and cattle aging I1 and I4 dentition. The collected data was analyzed by analysis of variance (ANOVA). Further differences between treatments were tested using Least Squared Mean (Lsmean). The results showed that buffalo and cattle meat have physical and histology characteristics has significantly (P <0.05). It is found that buffalo meat has lower water holding capacity and tenderness, and coarser texture compare to cattle at either I1 and I4 dentition.